Dietary vitamin D and calcium and periodontitis: A population-based study - Gustavo G. Nascimento; Gustavo G. Nascimento; Gustavo G. Nascimento; Fábio R. M. Leite; Fábio R. M. Leite; Fábio R. M. Leite; David A. Gonzalez-Chica; Karen G. Peres; Karen G. Peres; Marco A. Peres; Marco A. Peres (Frontiers in Nutrition, 2022)
AimThis study aimed to explore the relationship between dietary vitamin D and calcium intake and periodontitis among adults and whether it differs from males to females.MethodsCross-sectional analysis of a population-based cohort study with adults aged 20 to 60 from Southern Brazil. Intake of vitamin D and calcium were gathered in 2012 using two 24h-dietary recalls. Clinical examination assessed the clinical attachment level and bleeding on probing. Confounders included sex, age, family income, smoking, and obesity. The controlled direct effect of vitamin D and calcium on periodontitis was examined using marginal structural modeling. Analyses were also stratified by sex.ResultsOf the 1,066 investigated adults (mean age 35 ± 11.7 years; 49% females), 12.3% (95%CI 10.2;14.7) had periodontitis. Calcium intake had a direct protective effect on periodontitis (risk ratio (RR) 0.61; 95%CI 0.45;0.83), whereas no association between vitamin D and periodontitis was observed (RR 1.13; 95%CI 0.82;1.56). Stratified analyses revealed a null association between both vitamin D and calcium intake and periodontitis among men, but a protective association between calcium and intake and periodontitis among women (RR 0.56; 95%CI 0.38;0.79), while vitamin D remained without any association (RR 1.07; 95%CI 0.72;1.61).ConclusionOur findings suggest a protective association between dietary calcium intake and periodontitis among women.